Safe at home with Pooh : My very first Winnie the pooh - Zoehfeld, Kathleen Weidner; Cuddy, Robbin (New York : Disney Press, 1998)
Christopher Robin teaches Pooh and Piglet some of the safety rules regarding strangers.
O
b
b
Keywords: Picture Book -- Health and Selfcare